RITUAL PANYAMBLEH KUCIT BUTUAN DALAM UPACARA MECARU SASIH KAWULU DI JABA PURA DALEM DESA ADAT SANDING KECAMATAN TAMPAKSIRING KABUPATEN GIANYAR - I Made Restu Artama; Nerawati, Ni Gusti Ayu Agung (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
In carrying out rituals carried out by Hindus, of course they cannot be separated from the five basic beliefs called five yadnya. Such as the ritual of slaughtering needed kucit which is carried out by the people of the Sanding Traditional Village, which is one of the parts of the panca yadnya, especially the bhuta yadnya which is held once a year on Tilem Kawulu day, where this ritual is carried out at the Pura Dalem jaba of the Sanding Traditional Village as a form of treat or food given to the bhuta-bhuti and rarencang Ida Bhatara at Pura Dalem for the sake of safety and secrecy and protection of the universe. Based on the phenomena found in the implementation of panyambleh kucit butuan, it is very important to carry out research with the title